The Influence of Consumer Satisfaction and Confidence Against Repurchase of Computer Products in Surabaya - Artaya, I Putu; Kamisutara, Made (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2023)
The study of this research can draw implications for practitioners. From the results reported, there are three factors e-trust, e-satisfaction and e-loyalty that influence customers' online refurbishment intention at online stores. Cahaya Abadi Computer cares about trust as a signal to intend to repurchase online and satisfaction comes second. Therefore, online shops must first focus on the perceived trustworthiness of their online shopping and website. There are several ways to develop trust with e-commerce media. One of them is providing a safer payment system, data security and privacy policy. Also they use a more flexible warranty and keep in touch with customers in 7/24, current call/resolution center and reference to place e-trust. Second, online stores must respond to customer messages and complaints promptly and anticipate their needs earlier than competitors to satisfy and impress their customers. This research has shown that customers perceive e-loyalty as another important antecedent of online repurchase intention. Therefore, online stores can reward loyal customers to make them buy back by using promotional codes, discount codes, gift cards, providing special offers and daily offers.